Cam Jansen and the mystery of the Babe Ruth baseball - Adler, David A.; Natti, Susanna (New York : Dell, 1984)
Cam uses her photographic memory to identify the person who stole a valuable autographed baseball.
Elementary School Library Collection (Bro-Dart)
Booklist
School Library Journal
2.4
3-6
490
Keywords: Detective and mystery stories; Baseball stories; Mystery and detective stories; Baseball -- Fiction